La alteridad levinasiana y su analogía con el escepticismo (2017)
This article proposes to evaluate the idea of the philosopher Emmanuel Levinas according to which he proposes that alterity is similar to skepticism, as well as to determine if, in fact, Levinasian alterity is compromised with skepticism or if, on the contrary, it is a possibility to glimpse a renewed rationality in the discussion about the human. For this the analogy between alterity and skepticism is exposed; later, some answers given by scholars of the author are reviewed; finally, it is concluded by indicating some ways of reading the Levinasian alterity through the lens of a renewed rationality in the context of human Sciences.